Knowledge toward COVID‐19 in children among undergraduate students at the beginning of COVID‐19 era - Sawsan Abuhammad; Hossam Alhawatmeh; Ahlam Al‐Natour; Shaher Hamaideh; Nasr Alrabadi; Amer Sindiani; Amat Alkhaleq Mehrass (Nursing Open, 2023)
Abstract Aims To describe the level of knowledge of undergraduate students in Jordan toward COVID‐19 in children in respect of the clinical signs of the disease, modes of transmission, protection measures against the disease and satisfaction with governmental measures. Design A cross‐section was utilized in this study. Methods An online survey questionnaire was utilized in this research study. All undergraduate students in Jordan were able to take part. The size of the sample was 799. Knowledge toward COVID‐19 among children was used to assess the participants' knowledge about COVID‐19. Results The findings indicate that the students had a good understanding of the clinical signs, mode of transmission and protection measures and were satisfied with governmental measures. According to the students' responses, the resource they used the most was social media followed by news channels. Our study also found that medical specialty students had more knowledge toward COVID‐19 than non‐medical.